Communicating the potency of tourism: Study case of Wisata Bahari Lamongan - Khitam, Muhammad Chusnul; Suaedi, Falih; Asmorowati, Sulikah (Jurnal Studi Komunikasi, 2020)
This study aimed to determine the negotiation model and system of tourism partnership between the local government and the private sector to develop the â€œWisata Bahari Lamonganâ€ (WBL). This research used the qualitative method and negotiation theory part of public diplomacy. This research found that the negotiation and collaboration system used was the Public-Private partnership model with a built/operate/transfer (BOT) system. The private sector was allowed to build tourism facilities according to specified specifications. Then, the facility was built and operated by a private party for 25 years. After the period ended, Wisata Bahari Lamongan ownership was transferred to the local government.